2004
DOI: 10.1364/ol.29.002067
|View full text |Cite
|
Sign up to set email alerts
|

Defect modes in photonic crystal slabs studied using terahertz time-domain spectroscopy

Abstract: We describe broadband coherent transmission studies of two-dimensional photonic crystals consisting of a hexagonal array of air holes in a dielectric slab in a planar waveguide. By filling several of the air holes in the photonic crystal slab, we observe the signature of a defect mode within the stop band, in both the amplitude and phase spectra. The experimental results are in reasonable agreement with theoretical calculations using the transfer matrix method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…It is interesting to note that in a previous study employing a DF-PPWG, a similar positively chirped terahertz pulse has been observed, which has been attributed to a multimode effect due to the larger thickness of the dielectric (Si) slab. 5 Although multimode excitation is a possibility, based on the guided-wave model presented here, it is more likely that this chirped behavior was caused by the excitation of the TM 0 mode due to imperfect surface contacts.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…It is interesting to note that in a previous study employing a DF-PPWG, a similar positively chirped terahertz pulse has been observed, which has been attributed to a multimode effect due to the larger thickness of the dielectric (Si) slab. 5 Although multimode excitation is a possibility, based on the guided-wave model presented here, it is more likely that this chirped behavior was caused by the excitation of the TM 0 mode due to imperfect surface contacts.…”
mentioning
confidence: 90%
“…Backed by the simple planar geometry and excellent coupling to free-space radiation, PPWGs have been employed to study whispering-gallery modes, 3 to demonstrate interconnect layers, 4 to study photonic crystals, 5 to generate terahertz radiation, 6 for building biosensing systems, 7 and for guided-wave spectroscopy. 8 Most of these applications have sought to exploit the low loss, dispersionless characteristics of the dominant TEM mode, with the space between the plates filled with air 1,2 or some other form of dense medium such as a dielectric.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 More recently, cooling the PPWG to liquid nitrogen temperatures has enabled the measurement of linewidths as much as five times narrower than has been previously observed for a variety of thin organic films. 5 In addition to the above spectroscopic work, there have also been studies of the effect of photonic band gap ͑PBG͒ materials inside the waveguide with transmission through the PBG structure, 6,7 and alternatively in an air gap adjacent to the PBG structure. 8,9 The strong band gaps produced by these structures are useful for their filtering capabilities and also allow the opportunity to integrate defects.…”
mentioning
confidence: 99%
“…These parallel-plate structures have been used to demonstrate two-dimensional interconnect layers [3], sense nanometre water layers [4], study photonic crystals [5], and for building biosensing systems [6]. This Letter describes another novel use of these structures for the characterisation of highly conductive, optically dense materials resolving some of the fundamental problems associated with standard THz time-domain spectroscopy (THz-TDS) [7,8].…”
mentioning
confidence: 99%